Model Komunikasi dalam Debat di TvOne - Tomi Hendra; Indah Ramadhani (Institut Keislaman Abdullah Faqih Gresik, 2017)
This article explore about the Communication model in the debate program in TvOne. Thus is one of the news talk show programs which presents some speakers from the pros and cons in discussing a topic of problems or issues that are being warm, so that there is a process of communi-cation during the verbal and nonverbal impressions between the hosts with the speakers. This study aims, find out how the model of interactional communication debate in TvOne. Find out how the model of transactional communication debate in TvOne. This research uses qualitative content analysis method (content analysis) which focuses its research on the contents of the explicit communication. The results of the study can be concluded, overall program impres-sions TvOne debate describes the two process communication model is the model of interactional communication and transactional communication model. In the January 2016 edition of the debate, more identifiable models of transactional communication are identifiedKeywords: Communication Model and debate